Illuminating nitrogen transport: engineering biosensors for real-time monitoring in plants - Castro-Rodríguez, Vanessa; Floor, Martin; Robles, Ana; Ávila-Sáez, Concepción; Cánovas-Ramos, Francisco Miguel (My University, 2025)
Nitrogen (N) is a key player of plant growth and development, yet its excessive use in fertilizers leads to severe environmental consequences, including groundwater contamination and ecosystem disruption. Understanding nitrogen assimilation, transport, and biosynthesis at the cellular and subcellular levels is essential for optimizing plant productivity and sustainability. However, a major challenge persists: the lack of tools for real-time monitoring of nitrogen-related processes in living plants. To bridge this gap, we propose the development of dual ratiometric biosensors equipped with fluorescent proteins, designed to track nitrogen transport dynamics across different cellular compartments. Inspired by recent advances in biosensors in plants, our approach leverages key nitrogen transporters such as the ammonium transporter PpAMT1.3 from Pinus pinaster. By integrating these sensors, we aim to unveil the spatial distribution and functional mechanisms of nitrogen transporters at a level of resolution never before achieved. Studying ammonium transport in conifers is particularly relevant due to their dominance in temperate and boreal forests, where nitrogen availability is a limiting factor for growth. Unlike agricultural crops, conifers rely on highly efficient nitrogen uptake and recycling mechanisms to grow in nutrient-poor soils. Understanding how ammonium is transported and assimilated in these trees could provide critical insights for improving forest resilience, carbon sequestration, and sustainable management strategies in the face of climate change. This innovative strategy holds the potential to revolutionize plant nitrogen research, showing the way for more efficient nutrient use and sustainable agricultural practices, while offering valuable insights into plant physiology and real-time monitoring of nutrient dynamics, thus enhancing our understanding of plant responses and enabling more informed decision-making in agricultural management.‍
Illuminating nitrogen transport: engineering biosensors for real-time monitoring in plants Introduction: Carbon producers, nitrogen seekers Plants are remarkable organisms: they are autonomous carbon producers, yet they critically depend on the uptake of inorganic nitrogen from the environment. The coordination between carbon assimilation in photosynthetic tissues and nitrogen acquisition and mobilization from roots is therefore a central determinant of plant fitness, growth, and survival. The allocation of photoassimilates is not a passive process. It is dynamically regulated by light conditions, developmental programs, and long-distance shoot-derived signals, while nitrogen uptake and distribution are modulated by external cues such as nutrient availability, pH, drought, and carbon-to-nitrogen balance. Maintaining this equilibrium is essential, particularly under fluctuating environmental conditions. However, despite decades of research, our understanding of how nitrogen moves through the plant in space and time remains incomplete. One major reason is that nitrogen transport and metabolism are highly dynamic and strongly context-dependent. Cellular specialization and spatial diversity in nitrogen processing Nitrogen metabolism is not uniform across the plant. Different organs, tissues, cell types, and even subcellular compartments display specialized roles in nitrogen uptake, assimilation, storage, and remobilization. For example, roots and shoots exchange nitrogen predominantly in the form of amino acids, whose transport involves multiple interfaces: uptake from the soil, xylem loading, xylem–phloem transfer, phloem transport, and intracellular compartmentation within organelles such as vacuoles, chloroplasts, mitochondria, and the nucleus. This spatial and functional diversity implies that nitrogen mobilization mechanisms vary depending on developmental stage, environmental conditions, and physiological demand. Capturing these dynamics requires tools that go beyond static measurements and allow us to monitor nitrogen-related processes in vivo and in real time. Why real-time monitoring matters Traditional approaches to study nitrogen transport often rely on destructive sampling or bulk measurements that obscure spatial resolution and temporal dynamics. Yet nitrogen fluxes can change within seconds or minutes in response to environmental or developmental signals. Real-time monitoring of nitrogen compounds offers a powerful way to visualize how nutrients are sensed, transported, and redistributed within intact plants. This is particularly relevant when studying long-distance signaling, rapid responses to stress, or localized transport events at specific cellular interfaces. Genetically encoded biosensors: a window into plant nutrient dynamics Genetically encoded fluorescent biosensors have revolutionized our ability to study cellular processes in living systems. Since the discovery of GFP and its derivatives, these tools have been adapted to report metabolite concentrations, enzyme activities, ion fluxes, and signaling events with high spatial and temporal resolution. In plant science, biosensors allow us to: Monitor physiological, cellular, and molecular processes in vivo Target sensors to specific subcellular compartments Quantify dynamic changes rather than static pools Importantly, sensors can be expressed in specific tissues or cell types, enabling us to dissect nitrogen transport pathways at unprecedented resolution. Transporters as biosensor scaffolds: perfect candidates Membrane transporters are particularly attractive candidates for biosensor design. They possess high substrate specificity, defined concentration ranges, rapid response kinetics, and increasingly well-resolved structures. By engineering fluorescent proteins into transporter backbones, it is possible to convert nutrient transport activity into an optical signal. This strategy has been successfully applied to ammonium, nitrate, and amino acid transporters, allowing us to directly visualize nutrient fluxes rather than infer them indirectly. Rational design of nitrogen biosensors One example of this approach is the rational design of single-fluorophore sensors such as AmTrac, which reports ammonium transport activity in living cells. By systematically inserting fluorescent proteins at defined positions within the transporter, it is possible to identify sensor variants that respond sensitively and specifically to substrate binding or transport. This design strategy combines molecular biology, structural knowledge, and functional screening, and provides a versatile framework for developing new biosensors tailored to plant systems. Identifying biosensor gene candidates to decode plant fitness Looking forward, identifying suitable transporter and sensor gene candidates across different nitrogen pathways will be essential to fully decode plant fitness. By combining biosensors with targeted expression, subcellular localization, and advanced imaging, we can build a comprehensive picture of nitrogen dynamics across scales—from organelles to whole plants. Such approaches will not only deepen our fundamental understanding of plant nutrient biology but also provide tools with clear applications in agriculture, forestry, and sustainable bioeconomy strategies. Concluding remarks In summary, genetically encoded biosensors provide a powerful and versatile toolkit to illuminate nitrogen transport in plants. By enabling real-time, in vivo monitoring of nutrient dynamics, they allow us to move from static descriptions to dynamic, mechanistic understanding. Ultimately, integrating biosensor technology with plant physiology, molecular genetics, and systems biology will be key to addressing major challenges related to plant productivity, stress resilience, and sustainable resource use.
Keywords: Biosensores; Plantas; Nitrógeno; Biosensors; Nitrogen; Real-time monitoring